Synchrotron X‐ray diffuse scattering from a stable polymorphic material: terephthalic acid, C8H6O4. Issue 1 (1st February 2017) - Goossens, D. J.; Chan, E. J.
Abstract : A model for the X‐ray diffuse scattering from terephthalic acid (C8 H6 O4 ) is presented, and used to explore the sensitivity of diffuse scattering to polymorphic interconversion, and to demonstrate the relative ease with which the harmonic (`thermal') component of the diffuse scattering can be modelled. Abstract : Terephthalic acid (TPA, C8 H6 O4 ) is an industrially important chemical, one that shows polymorphism and disorder. Three polymorphs are known, two triclinic [(I) and (II)] and one monoclinic (III). Of the two triclinic polymorphs, (II) has been shown to be more stable in ambient conditions. This paper presents models of the local order of polymorphs (I) and (II), and compares the single‐crystal diffuse scattering (SCDS) computed from the models with that observed from real crystals. TPA shows relatively weak and less‐structured diffuse scattering than some other polymorphic materials, but it does appear that the SCDS is less well modelled by a purely harmonic model in polymorph (I) than in polymorph (II), according to the idea that the diffuse scattering is sensitive to anharmonicity that presages a structural phase transition. The work here verifies that displacive correlations are strong along the molecular chains and weak laterally, and that it is not necessary to allow the —COOH groups to librate to successfully model the diffuse scattering – keeping in mind that the data are from X‐ray diffraction and not directly sensitive to H atoms.